2021
DOI: 10.1021/acs.joc.1c00777
|View full text |Cite
|
Sign up to set email alerts
|

BN/BO-Ullazines and Bis-BO-Ullazines: Effect of BO Doping on Aromaticity and Optoelectronic Properties

Abstract: We have achieved substitutional doping of ullazine with either two BO units or with one BO unit and one BN unit. The synthesis of these B-doped ullazines is straightforward, using demethylation and borylative cyclization as the key steps. Ullazine cores of both BN/BO-ullazines (2) and bis-BO-ullazines (3) are very close to being planar. Their electronic and photophysical properties were investigated by ultraviolet− visible, fluorescence spectroscopy, cyclic voltammetry, and density functional theory calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…The corresponding voltammograms are shown in Figure . Both compounds follow the redox behavior of 1- and 2-azapyrene by irreversible oxidation events within the potential window of DCM. , The same electrochemical oxidation behavior is observed for other nitrogen-containing pyrene analogs, e.g., 4,9- and 4,10-diazapyrenes, (aza)-ullazine, , BN -and BN/BO-ullazines , as well as for the carbon analog pristine PLT, which excludes N-doping-specific effects on the redox nature of TNP . The oxidation peak potential of TNP-3a is found to be E (ox) = 0.92 V against the Fc/Fc + redox couple and ascribed to an oxidation event at the TNP core connected with the formation of the TNP •+ radical cation.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…The corresponding voltammograms are shown in Figure . Both compounds follow the redox behavior of 1- and 2-azapyrene by irreversible oxidation events within the potential window of DCM. , The same electrochemical oxidation behavior is observed for other nitrogen-containing pyrene analogs, e.g., 4,9- and 4,10-diazapyrenes, (aza)-ullazine, , BN -and BN/BO-ullazines , as well as for the carbon analog pristine PLT, which excludes N-doping-specific effects on the redox nature of TNP . The oxidation peak potential of TNP-3a is found to be E (ox) = 0.92 V against the Fc/Fc + redox couple and ascribed to an oxidation event at the TNP core connected with the formation of the TNP •+ radical cation.…”
Section: Resultsmentioning
confidence: 55%
“…7.92 (dd, J = 3.0 Hz, J = 1.3 Hz, 1H), 7.65 (dd, J = 4.9 Hz, J = 1.3 Hz, 1H), 7.29−7.48 (m, 11H). 13 (51), 207 (15), 163 (22), 150 (15), 135 (15), 126 (29), 77 (77), 76 (14), 74 (16), 73 (74), 63 (20), 51 (27), 45 (36), 39 (23) (46), 387 (11), 375 (15), 374 (50), 373 (42), 372 (12), 359 (13), 187 (10), 186 (9), 179 (8), 170 (8) (53), 375 (18), 374 (57), 373 (61), 372 (19), 359 (18), 207 (17), 139 (33), 91 (48), 89 (20), 77 (28), 75 (18), 73 (76), 65 (42), 63 (19), 51 (20), 39 (35) (73), 371 (47), 340 (13), 339 (19), 328 (32), 169…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Representative synthetic routes for 1,2-oxaborinine derivatives are shown in Figure . Dewar et al pioneeringly reported that dibenzo­[ c , e ]­[1,2]­oxaborinin-6-ols are formed from the electrophilic borylation of 2-phenylphenol, wherein the strong Lewis acids BCl 3 and AlCl 3 are required (Figure a). Nicholson et al also demonstrated that the benzo­[ c ]­[1,2]­oxaborinin-1-ol product is obtained from the reaction of 1-(4-methoxyphenyl)-2-phenylbutan-1-one with BBr 3 (Figure a) . Benhamou and Sheppard et al showed that palladium catalyzes the cyclization of 2-alkynyl-phenyl-boronic acids with allyl chlorides to afford the corresponding 4-allylated benzo­[ c ]­[1,2]­oxaborinin-1-ols (Figure b) .…”
mentioning
confidence: 99%